Full-endoscopic interlaminar approach for L5-S1 extruded and migrated central hernias. Case series study - Ramírez-León, Jorge Felipe; Rugeles-Ortiz, José Gabriel; Prada-Ramírez, Nicolás; Ramírez-Martínez, Carolina; Alonso-Cuéllar, Gabriel Oswaldo (Revista Colombiana de ortopedia y traumatología, 2020)
Background: Endoscopic spine surgery has shown to be an option for disc hernias and foraminal stenosis. Although the most used approach is transforaminal, this approach is limited in cases of extruded and migrated central hernias. The full-endoscopic interlaminar approach has led to the treatment of the lumbar pain secondary to extruded and migrated central herniated discs at L5 - S1, and is an alternative for resolving technical difficulties related to the transforaminal approach at this level. The aim of this article is to report the results obtained with a fullendoscopic interlaminar approach for the treatment of central extruded and migrated herniated discs, with a two-year follow-up. Methods: A descriptive observational retrospective study was conducted using the records of patients who had a radiculopathy secondary to a central herniated disc at level L5 - S1, and who were treated with a full-endoscopic interlaminar approach. An evaluation was made of the pre-operative and post-operative visual analogue scale (VAS) scores, Oswestry ODI criteria, and MacNab criteria. Results: A total of 99 procedures were performed in the same number of patients between 2008 and 2015. All were treated with a standard surgical technique and under local anaesthesia and sedation. The visual analogue score showed a reduction of 5.81 points. The ODI was down 45.63%, and 88% of the patients were completely satisfied with the treatment. Discussion: The results lead us to consider that full-endoscopic interlaminar fragmentectomy under local anaesthesia and sedation is a safe, accurate, and effective procedure for the treatment of radiculopathy related to L5 - S1 extruded and migrated central hernia. Use of local anaesthesia and sedation as the only analgesic alternative may not be the best option in this type of technique. Evidence Level: IV